Antagonistic relationship between the unfolded protein response and myocardin‐driven transcription in smooth muscle. Issue 10 (10th February 2020) - Zhu, Baoyi; Daoud, Fatima; Zeng, Shaohua; Matic, Ljubica; Hedin, Ulf; Uvelius, Bengt; Rippe, Catarina; Albinsson, Sebastian; Swärd, Karl
Abstract: Smooth muscle cells (SMCs) are characterized by a high degree of phenotypic plasticity. Contractile differentiation is governed by myocardin‐related transcription factors (MRTFs), in particular myocardin (MYOCD), and when their drive is lost, the cells become proliferative and synthetic with an expanded endoplasmic reticulum (ER). ER is responsible for assembly and folding of secreted proteins. When the load on the ER surpasses its capacity, three stress sensors (activating transcription factor 6 [ATF6], inositol‐requiring enzyme 1α [IRE1α]/X‐box binding protein 1 [XBP1], and PERK/ATF4) are activated to expand the ER and increase its folding capacity. This is referred to as the unfolded protein response (UPR). Here, we hypothesized that there is a reciprocal relationship between SMC differentiation and the UPR. Tight negative correlations between SMC markers ( MYH11, MYOCD, KCNMB1, SYNPO2 ) and UPR markers ( SDF2L1, CALR, MANF, PDIA4 ) were seen in microarray data sets from carotid arterial injury, partial bladder outlet obstruction, and bladder denervation, respectively. The UPR activators dithiothreitol (DTT) and tunicamycin (TN) activated the UPR and reduced MYOCD along with SMC markers in vitro. The IRE1α inhibitor 4μ8C counteracted the effect of DTT and TN on SMC markers and MYOCD expression. Transfection of active XBP1s was sufficient to reduce both MYOCD and the SMC markers. MRTFs also antagonized the UPR as indicated by reduced TN and DTT‐mediated induction of CRELD2, MANF, PDIA4, and SDF2L1 following overexpression of MRTFs. The latter effect did not involve the newly identified MYOCD/SRF target MSRB3, or reduced production of either XBP1s or cleaved ATF6. The UPR thus counteracts SMC differentiation via the IRE1α/XBP1 arm of the UPR and MYOCD repression. Abstract : Smooth muscle differentiation and the unfolded protein response represent distinct gene programs necessary for homeostasis. This study shows that these gene programs are antagonistic in several in vivo models, and that this is due in part to repression of myocardin by XBP1s.